High efficiency multi power source control constant current/constant voltage charger lithium-ion battery based on the buck converter - Ismail Boumedra; Abdelamin Diani; Karim El Khadiri; Ahmed Tahiri; Mohammed Ouazzani Jamil; Hassan Qjidaa (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This paper proposes the design and simulation of a constant current/constant voltage (CC/CV) multi-power source lithium-ion (Li-ion) battery charging system based on the Buck typology. The aim of this new design that uses the Buck converter with multiple numbers of sources, is to provide sufficient energy for battery charging, with an analog switch to select the active source that has priority to guarantee the continuity of the charging without interruption. As well as the transition between the charging modes is smooth that is provided by a multiplexed switcher. At the same time is increases the efficiency of the system by using fewer power dissipation components and low output ripple. The obtained results show that the Li-ion battery can be successfully charged without reducing its life cycle. In the global, those technics allow reducing financial costs. This allows such a solution to be well-positioned in the industrial market (electric vehicles (EV) and medical).